2017
DOI: 10.1111/1750-3841.13711
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Tuna Dark Muscle Protein Attenuates Hepatic Steatosis and Increases Serum High‐Density Lipoprotein Cholesterol in Obese Type‐2 Diabetic/Obese KK‐Ay Mice

Abstract: Tuna muscle consists of light and dark muscle in approximately equal proportions. However, besides for the light muscle of tuna, cod, sardine, and salmon, few researches have assessed the health-promoting functions of fish protein. Therefore, we evaluated the mechanisms underlying the alteration of lipid storage and cholesterol metabolism following the intake of tuna dark muscle protein (TDMP) by obese type-2 diabetic/obese mice. Four-week-old male KK-A mice were separated into 2 dietary groups, with one group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 55 publications
(55 reference statements)
0
23
0
Order By: Relevance
“…Highly nutritious lean fish protein is abundantly present in fish and consumed worldwide including in processed foods such as artificial crab, kamaboko (fish cakes), and fish sausages. Previously, studies from our laboratory and others showed that fish proteins from Alaska pollock, tuna, and tuna dark muscle, ameliorate hypercholesterolemia and nonalcoholic fatty liver disease (Hosomi et al., 2015, 2017; Maeda et al., 2017) and prevent obesity, hypercholesterolemia, and hypertension (Drotningsvik et al., 2018; Oishi & Dohmoto, 2009; Yathisha, Bhat, Karunasagar, & Mamatha, 2019). In addition, cod protein reduced fasting and postprandial glucose levels and increased peripheral insulin sensitivity compared to casein, in rats fed a high‐sucrose diet (Lavigne, Marette, & Jacques, 2000).…”
Section: Introductionmentioning
confidence: 96%
“…Highly nutritious lean fish protein is abundantly present in fish and consumed worldwide including in processed foods such as artificial crab, kamaboko (fish cakes), and fish sausages. Previously, studies from our laboratory and others showed that fish proteins from Alaska pollock, tuna, and tuna dark muscle, ameliorate hypercholesterolemia and nonalcoholic fatty liver disease (Hosomi et al., 2015, 2017; Maeda et al., 2017) and prevent obesity, hypercholesterolemia, and hypertension (Drotningsvik et al., 2018; Oishi & Dohmoto, 2009; Yathisha, Bhat, Karunasagar, & Mamatha, 2019). In addition, cod protein reduced fasting and postprandial glucose levels and increased peripheral insulin sensitivity compared to casein, in rats fed a high‐sucrose diet (Lavigne, Marette, & Jacques, 2000).…”
Section: Introductionmentioning
confidence: 96%
“…The loss of BW in the APP + DSS group was significantly lower on Day 8 compared with the CAS + DSS group (Figure 1A). The APP + DSS group had a significantly lower DAI score on Day 10,12,16,22, and 24 than the CAS + DSS group (Figure 1B). The area under the curve (AUC) of the DAI score in the APP + DSS group was significantly lower than that of the CAS + DSS group (Figure 1C).…”
Section: App Intake Alleviates Experimental Colitis Symptoms Induced ...mentioning
confidence: 97%
“…In addition to fat, fish is also rich in nutritious protein [15]. Our previous studies have suggested that proteins prepared from several fish species protect against the accumulation of triacylglycerol in the liver [16,17] and reduce the level of serum cholesterol [18]. Other researchers have reported that Alaska pollock protein (APP) exhibits beneficial effects on obesity [19] and muscle hypertrophy [20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Chi et al found that protein hydrolysates of tuna dark muscle presented significant radical scavenging and lipid peroxidation inhibition ability ( 28 ). Maeda et al revealed that the dietary tuna dark muscle could decrease hepatic steatosis and promote serum high-density lipoprotein cholesterol in obese type-2 diabetic/obese KK-A (y) mice ( 29 ).…”
Section: Introductionmentioning
confidence: 99%